ENERGY-EFFICIENT POWER ELECTRONICS: DESIGN STRATEGIES FOR SUSTAINABLE ELECTRICAL ENGINEERING - Muhammad Firdaus Abduh; Anna Schneider; James Smith (Journal of Moeslim Research Technik, 2026)
Increasing global energy demand, rapid electrification, and growing environmental concerns have intensified the need for energy-efficient technologies capable of supporting sustainable development. Power electronics plays a crucial role in modern electrical engineering by enabling efficient energy conversion, transmission, and utilization across renewable energy systems, electric vehicles, smart grids, and industrial applications. Persistent challenges related to switching losses, thermal dissipation, and converter inefficiencies continue to limit overall system performance and sustainability outcomes. This study aims to examine design strategies that enhance energy efficiency in power electronic systems and to evaluate their contribution to sustainable electrical engineering. A qualitative literature-based research design employing a systematic review approach was adopted. Relevant peer-reviewed publications published between 2015 and 2025 were analyzed to identify emerging technological trends, efficiency-enhancing mechanisms, and sustainability-oriented design principles. Findings indicate that advanced semiconductor technologies, particularly silicon carbide (SiC) and gallium nitride (GaN), significantly reduce power losses and improve conversion efficiency. Optimized converter topologies, intelligent control algorithms, and advanced thermal management systems further enhance system reliability and operational performance. Integrated implementation of these strategies produces greater efficiency gains than isolated technological improvements. The study concludes that sustainable electrical engineering requires a holistic design framework that combines technological innovation, system optimization, and environmental considerations. Such an approach can accelerate the development of highly efficient, reliable, and environmentally responsible electrical energy systems.